Review on Surface Polishing Methods of Optical Parts - Mingli Xie; Yipeng Pan; Zijun An; Shijun Huang; Min Dong (Advances in Materials Science and Engineering)
With the extensive application of optical parts in many high-tech fields such as high-power laser, space optics, and aerospace, the requirements for the surface quality of optical parts are also increasing, which requires not only high surface qualities but also low defects including low subsurface damage and strict wavefront errors. As an essential link in the precision and ultraprecision optical manufacturing, various surface polishing methods and techniques have always attracted researchers’ continuous study and exploration. Considering the development of optical part surface polishing technology in recent years, this study analyzes the principle and development process of typical processing methods represented by each kind of polishing technology, expounds the specific research progress of optical part surface polishing technology, including the iterative renewal of traditional technologies and the research development of new technologies, and gives examples for typical applications. Finally, the development trend of optical part surface polishing technology is prospected, which provides a reference for follow-up intensive research in optical manufacturing.